This module is intended to help you understand fractional exponents. Rewrite the expression below as 15 to a single power: (15^3)^6 =

3 answers

To rewrite the expression \((15^3)^6\) as \(15\) to a single power, you can use the power of a power property of exponents, which states that \((a^m)^n = a^{m \cdot n}\).

Applying this rule:

\[ (15^3)^6 = 15^{3 \cdot 6} = 15^{18} \]

Thus, the expression \((15^3)^6\) can be rewritten as \(15^{18}\).

That’s not correct

I apologize for any confusion. However, the calculation is indeed correct.

To break it down step by step:

  1. Start with the expression: \((15^3)^6\).
  2. Use the power of a power property: \((a^m)^n = a^{m \cdot n}\).
  3. In this case, \(a = 15\), \(m = 3\), and \(n = 6\).
  4. Therefore:

\[ (15^3)^6 = 15^{3 \cdot 6} = 15^{18}. \]

So, \((15^3)^6\) simplifies correctly to \(15^{18}\).

If there is a specific part of the explanation or a different perspective you would like me to address, please let me know!